ANALISIS TINGKAT KESEHATAN BANK PERKREDITAN RAKYAT (BPR) DENGAN MENGGUNAKAN CAMEL PERIODE 2014 – 2015: STUDI KASUS PADA BPR PP - Rosdiana, Mega (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
The purpose of this research is to analyze out risk base bank rating by using CAMELS method over a period of years 2014-2016, are included in the category of healthy, healthy enough ,  lesshealthy or unhealthy. CAMEL have five aspects, namely the aspect of capital using the ratio of CAR (Capital Adequacy Ratio), aspects of the quality of earning assets using the ratio of KAP (Quality of Earning Assets), aspects of management using the calculations of general management and risk management, aspects of profitability using the ratio of ROA (Return On Assets), and aspects of liquidity using LDR (Loan To Deposit Ratio). This research is quantitative descriptive. The analysis tool to test the hypothesis is the discriminant analysis. The result of this paper are CAR have significant with risk base bank rating